Nestin is expressed in basal-like and triple negative breast cancers. Issue 9 (19th July 2008) - Parry, S; Savage, K; Marchiò, C; Reis-Filho, J S
Abstract : Aims: To analyse the distribution of nestin expression in different breast tumours and to determine the prognostic impact of nestin expression. Methods: Nestin expression was immunohistochemically analysed in a cohort of 245 invasive breast cancer patients treated with therapeutic surgery followed by anthracycline-based chemotherapy using a semi-quantitative scoring system. Results: Nestin was exclusively expressed in grade III breast carcinoma and preferentially expressed in basal-like and triple negative cancers. Nestin-positive tumours displayed high proliferation rates and p53 nuclear expression. Lymph-node positive patients with nestin-positive cancers had a shorter breast cancer specific survival; however nestin was not an independent prognostic factor on multivariate analysis. Conclusions: Nestin expression is preferentially found in basal-like and triple negative breast carcinomas. Further studies are warranted to define the biological role played by nestin in these subgroups of breast cancers.